2020
DOI: 10.1186/s12966-020-00957-0
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and complexity of interventions targeting sedentary behaviour across the lifespan: a systematic review and meta-analysis

Abstract: Background: Evidence suggests that sedentary behaviour (SB) is associated with poor health outcomes. SB at any age may have significant consequences for health and well-being and interventions targeting SB are accumulating. Therefore, the need to review the effects of multicomponent, complex interventions that incorporate effective strategies to reduce SB are essential. Methods: A systematic review and meta-analysis were conducted investigating the impact of interventions targeting SB across the lifespan. Six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 200 publications
4
55
1
Order By: Relevance
“…Following the seminal intervention study conducted two decades ago that aimed to reduce leisure screen-time in American elementary school children [38], previous evidence, mostly derived from high-income countries, have found that interventions aimed at reducing sedentary behavior in young people show small but statistically significant effects [39]. Most promising strategies to reduce sedentary behavior were multi-component strategies including behavioral (e.g., focused on theory driven approaches), and environmental (e.g., aim to modify home, school, or facilities) approaches, interventions that were conducted in community settings, and those that included the involvement of family members [39,40]. More research regarding key features or effective interventions for reducing adolescent's sedentary behavior is needed from more culturally diverse settings including LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…Following the seminal intervention study conducted two decades ago that aimed to reduce leisure screen-time in American elementary school children [38], previous evidence, mostly derived from high-income countries, have found that interventions aimed at reducing sedentary behavior in young people show small but statistically significant effects [39]. Most promising strategies to reduce sedentary behavior were multi-component strategies including behavioral (e.g., focused on theory driven approaches), and environmental (e.g., aim to modify home, school, or facilities) approaches, interventions that were conducted in community settings, and those that included the involvement of family members [39,40]. More research regarding key features or effective interventions for reducing adolescent's sedentary behavior is needed from more culturally diverse settings including LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…This attraction may explain why sedentary behaviors are di cult to avoid (Cheval et al, 2020; and why motivational precursors alone can hardly prevent engagement in sedentary behaviors. In this view, environmental interventions (e.g., nudges) have proven to be more effective in reducing sedentary behaviors than interventions targeting motivational variables (Blackburn et al, 2020;Gardner et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, interventions should begin early and target all these behavioural and environmental domains. Interventions to reduce sedentary time in children have been fairly successful in short term (<6 months) as well as in long term (≥6 months) studies (−25.9 (95% CI −40.8, −11.0) min and −14.0 (95% CI −19.5, −8.6) min, respectively) [35].…”
Section: Discussionmentioning
confidence: 99%